CONTRIBUTION OF RESETTLEMENT PROJECTS TO PERI-URBAN EXPANSION-A CASE OF PUGU KINYAMWEZI, RESETTLEMENT AREA IN DAR ES SALAAM CITY (The Journal of Building and Land Development, 2023)
Urban development projects may cause land use changes which can lead to compulsory land acquisition, tenure change, displacements and resettlements. These projects intend to improve cities/large towns. The change of tenure led into direct control by developer to land previously occupied. The projects also cause development-induced displacement and resettlement on previous developments that require land expropriation. This paper describes contribution of urban projects into urban expansions. Methodology used include interviews, Focus Group discussions, mapping, observations and photographic registration in one of the resettlement areas, Pugu-Kinyamwezi, in Dar es Salaam city. Findings show that the process of displacement and resettlement, contributed into peri-urbanization amidst urban expansions in areas where the displaced population is resettled. In most cases due to land in-availability, areas for resettlement projects are often in the Peri-urbans. Changes in population and land use have direct effect on urban expansion. Peri- urban area spreads into rural areas causing population and economic growth which creates demand for housing and commercial areas. To speed up the urban expansion process people can acquire land for investment purposes such as commercial facilities, retail, and wholesale points as well as housing estates for residential purposes since its value is not as high as it might be in urban areas.Â Key Words: Dar es Salaam, peri urban, resettlement, urbanization, urban expansion